Biomechanical characteristics of V1 skate technique of elite Nordic combined skiers - Novikova, N. B.; Zakharov, G. G.; Voronov, A. V. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to analyze the V1 skate ski double poling competitive techniques of the world Nordic combined elite.